Struktur Pembentuk Modalitas Ajakan Mashouka Serta Maknanya - Rini Puji Astuti; Shofiyya Qonitina Dienillah; Dwinda Rizca Hartono; Akmal Syuhada (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2023)
The mashouka form is a change of mashou form which is changed into a question form, only has the meaning of guru-pu gata no kanyuu which means collective invitation and does not have the meaning of hikikomi gata no kanyuu (invitation in the form of force). This study aims to find out the structure that forms the meaning of mashouka and the meaning it creates. Therefore, the research uses descriptive method to make descriptive data in the form of description or painting, factual and accurate about the facts, characteristics and relationships of the phenomena to be studied. The descriptive method will also facilitate the presentation of data results. The invitation form mashouka is a kanyuu hyougen of the shiyouka group. Structurally, it is a shiyou form of verb which is then converted into a question form (interrogative). The shiyouka invitation form belongs to the guru-pu gata no kanyuu group (collective invitation) which does not contain coercion. Usually, the form of invitation in Japanese is often accompanied by a persona pronomina either clearly or implicitly. The meaning arising from the use of this form of mashouka invitation emphasizes the speaker's desire to perform an action together / as a group.